Servant Leadership and Organizational Commitment: Demographic Comparison between Local Bankers and Foreign Bankers in Malaysia - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan (Globeedu Group, 2018)
This noble intention of this paper is to highlight the demographic comparison between bankers in the local and foreign banks in Malaysia, specifically in the state of Perlis, Kedah, Penang, and northern Perak. Three-hundred questionnaires were distributed among the bankers in the above four states. Thus, a good response rate of 61% was clocked by this paper. This paper adapted servant leadership instrument from Van Dierendonck & Nuijten. On the other hand, the organizational commitment had been adopted from Meyer and Allen. This paper provides a good understanding of the servant leadership among bankers of local and foreign banks which could benefit the banks' top management in promoting their employees' productivity and in turn translated into the banks' profitability